The Relationship of Midwives' Knowledge About Hypnobreastfeeding and Lactation Massage with the Motivation of Providing Information by Midwives to Mothers for Breastfeeding - Farrah Lisa, Ulfa; Mutiara Halida, Erda; Yulizawati, Yulizawati; Ayunda Insani, Aldina (CV. Green Publisher Indonesia, 2024)
The breastfeeding support is crucial for nursing mothers, and one aspect of this support is the motivation provided by healthcare professionals in delivering maternity services to breastfeeding mothers, particularly regarding hypnobreastfeeding and lactation massage. An individual's motivation is significantly influenced by their knowledge of specific subjects. This quantitative research employed an analytical method, utilizing a cross-sectional design. The study was conducted in the Maternal and Child Health Center of Padang City from September to October 2023. The research sample consisted of 40 midwives working in the Maternal and Child Health Center in Padang. The analysis used the chi-square test with a confidence interval of 95%. The research findings indicate that the majority of participants with insufficient knowledge about hypnobreastfeeding had low motivation (41.17%), compared to those with high motivation (8.70%). The statistical test result using the chi-square test yielded a p-value of 0.035 (p≤0.05). Meanwhile, in terms of knowledge about lactation massage, the majority with insufficient knowledge had low motivation (23.53%), while those with high motivation had no insufficient knowledge (0%). The statistical test result using the chi-square test yielded a p-value of 0.046 (p≤0.05). Therefore, it can be concluded that there is a significant relationship between knowledge about hypnobreastfeeding and lactation massage and the motivation of midwives to provide information